Hypocreodendron sanguineum - Sanchez, Romina Magali (2023)
Hypocreodendron sanguineum is saprobic on waste material of ant nests, presumably of some species of the genera Atta and Acromyrmex. The fungus has been found predominantly associated with waste piles outside the nests in areas with temperate to subtropical climates that go through a drier stage during the year, with most records in or near urban areas. Even though it could occur along its hosts' distribution, it has only been reported a small number of times. With a long history of mycological studies in Latin America and with a striking fungal appearance (stromata 2.5 cm high with a red apical disc) this fungus has only been recorded in 13 sites, mostly in Mexico and Argentina, but also in Brazil, Guatemala, and Uruguay. The habitat of this fungus could be under high levels of disturbance because of the destruction of the ant nests primarily by pesticides and secondarily by the construction of roads and firewalls. Further targeted surveys within the range of its ant hosts will be required to better understand the status and trend of H. sanguineum, as well as to delimit its true range. Without such further information it is not possible to accurately assess its extinction risk. Therefore, the present assessment is Data Deficient (DD).